PERBANDINGAN TEPUNG JAGUNG DENGAN TEPUNG TERIGU SERTA PENAMBAHAN CMC TERHADAP KARAKTERISTIK MI JAGUNG - Yonatan Umbu Pingge; A A Made Semariyani; I Putu Candra (GEMA AGRO, 2021)
Noodles are a food product that is widely consumed by Indonesians. Noodle products, in the form of wet noodles, dry noodles, and instant noodles, have now become the second main food ingredient for Indonesians after rice. The practical nature of noodles makes it easy for consumers to process them into various dishes (Larasati, 2015). However, consumption of noodles has the opportunity to reduce the country's foreign exchange because noodles are made from wheat flour, an imported commodity. The choice of corn as a substitute for wheat flour is because corn is a commodity that contains adequate nutritional value. This study aims to determine the ratio of corn flour to wheat flour and the addition of CMC to the characteristics of corn noodles. The design used was a completely randomized design (CRD) factorial pattern with two factors and two replications, namely the first factor, the ratio of corn flour to wheat flour consisting of 4 levels: (100: 0), (80:20), (70: 30), (60:40). The second factor was the addition of CMC which consisted of 4 levels, namely: (1%), (2%), (%), (4%). Observations were carried out objectively including: moisture content, ash content, fat content, protein content. Meanwhile, subjective observations include: color, texture, taste and overall acceptance. The best research results were obtained in the treatment of 70% corn flour and 30% wheat flour with the addition of 1% CMC with the results of 67,39% water content, 1,00% ash content, 3,92% fat content, 6,14% protein content, and subjectively get the highest favorite score. Compared with the Indonesian National Standard (SNI) No. 2987-2015), it is found that the treatment has met the quality requirements. Except for the value of water content and ash content which are still high, and are still accepted by consumers.